Medical Insurance Plan Assistant Expert System - Siek Leng, Tan; Shin Yee, Wong; Yee Ling, Chan; Surip, Miswan; Aryanie Bahrudin, Ida; Halim Omar, Abdul; Hanif Jofri, Muhammad; Md Yasin, Suhaimi (International Journal of Engineering and Technology, 2026)
The increase of the uncertainty factor in future has led more and more people to seek security when they are in suffer by subscribing to insurance policy. However, purchasing an insurance policy is not something just filling in some forms and pays it this is because insurance company provides different kind of policy that suits different needs of people even it is still the same for medical insurance policies. Therefore, the Medical Insurance Plan Assistant Expert System was developed to help those who are interested in purchasing a medical insurance policy by suggesting the suitable medical or health insurance policy. This system will ask several requirements or criteria that will be the source of information for the inference engine of this system to generate answer.
Keywords: Expert System; Insurance plan; Insurance policy.